High Glucose Activates YAP Signaling to Promote Vascular Inflammation - Ortillon, Jeremy; Le Bail, Jean-Christophe; Villard, Elise; Léger, Bertrand; Poirier, Bruno; Girardot, Christine; Beeske, Sandra; Ledein, Laetitia; Blanchard, Véronique; Brieu, Patrice; Naimi, Souâd; Janiak, Philip; et al. (Frontiers in Physiology, 2021)
Background and aims. The YAP/TAZ signaling is known to regulate endothelial activation and vascular inflammation in response to shear stress. Moreover, YAP/TAZ signaling plays a role in the progression of cancers and renal damage associated with diabetes. However, whether YAP/TAZ signaling is also implicated in diabetes-associated vascular complications is not known. Methods. The effect of high glucose on YAP/TAZ signaling was firstly evaluated in vitro on endothelial cells cultured under static conditions or subjected to shear stress (either laminar or oscillatory flow). The impact of diabetes on YAP/TAZ signaling was additionally assessed in vivo in db/db mice. Results. In vitro, we found that YAP was dephosphorylated/activated by high glucose in endothelial cells, thus leading to increased endothelial inflammation and monocyte attachment. Moreover, YAP was further activated when high glucose was combined to laminar flow conditions. YAP was also activated by oscillatory flow conditions but, in contrast, high glucose did not exert any additional effect. Interestingly, inhibition of YAP reduced endothelial inflammation and monocyte attachment. Finally, we found that YAP is also activated in the vascular wall of diabetic mice, where inflammatory markers are also increased. Conclusions. With the current study we demonstrated that YAP signaling is activated by high glucose in endothelial cells in vitro and in the vasculature of diabetic mice, and we pinpointed YAP as a regulator of high glucose-mediated endothelial inflammation and monocyte attachment. YAP inhibition may represent a potential therapeutic opportunity to improve diabetes-associated vascular complications.